How do the Green Energy Stocks React to Green Bond Issuances? - Yavuz Gül; Mehmetcan Suyadal (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Achieving sustainable development is one of the main issues at the global level and both public and private sector enterprises need to make large – scale investments to fight against climate change. In this respect, green bonds gain importance to raise money for environmentally – friendly projects, especially clean energy. Proceeds from green bonds are earmarked towards financing of investments that have positive environmental impacts. This paper explores the relationship among green bond issuances and stock market reaction with special focus on renewable energy firms. Herein, through a dataset of green bond issuance announcements worldwide by 46 unique firms over the period from 2014 to 2023, we investigate how the share prices respond to such announcements using event – study methodology. From the empirical evidence of the downward stock price movements, we suggest that investors react negatively to the announcement of green bond issuances. In other words, we find significant and negative cumulative average abnormal returns (CAAR) across all the event windows except in the window of [0, 10], meaning that our findings are robust to several alternative event windows. Further, we determine that the share price response, in general, does not differ depending on the use of green bond proceeds and the years.